Oxidation of Sodium Deoxycholate Catalyzed by Gold Nanoparticles and Chiral Recognition Performances of Bile Salt Micelles - Wang, Jing (Molecules, 2019)
Au nanoparticles (NPs) were prepared by UV light irradiation of a mixed solution of HAuCl(4) and sodium deoxycholate (NaDC) under alkaline condition, in which NaDC served as both reducing agent and capping agent. The reaction was monitored by circular dichroism (CD) spectra, and it was found that the formed gold NPs could catalyze the oxidation of NaDC. A CD signal at ~283 nm in the UV region was observed for the oxidation product of NaDC. The intensity of the CD signal of the oxidation product was enhanced gradually with the reaction time. Electrospray ionization (ESI) mass spectra and nuclear magnetic resonance (NMR) spectra were carried out to determine the chemical composition of the oxidation product, revealing that NaDC was selectively oxidized to sodium 3-keto-12-hydroxy-cholanate (3-KHC). The chiral discrimination abilities of the micelles of NaDC and its oxidation product, 3-KHC, were investigated by using chiral model molecules R,S-1,1′-Binaphthyl-2,2′-diyl hydrogenphosphate (R,S-BNDHP). Compared with NaDC, the micelles of 3-KHC displayed higher binding ability to the chiral model molecules. In addition, the difference in binding affinity of 3-KHC micelles towards R,S-isomer was observed, and S-isomer was shown to preferentially bind to the micelles.